New Life Transition of Former Caregivers: Positive Mental Health Approach - Mora-Lopez, Gerard; Berenguer-Poblet, Marta; Berbis-Morelló, Carme; Albacar-Rioboo, Nuria; Montesó-Curto, Pilar; Aguaron-García, María Jesús; Ferré-Grau, Carme (Frontiers in Psychology, 2022)
After the end of their time as a caregiver, former caregivers have needs and feelings that have been subject to little study to date. The aim of the study is to determine and analyse the feelings, perceptions and practices of former caregivers in the reconstruction of their daily lives. This is a qualitative study based on the Grounded Theory developed by Charmaz. The study involved 14 former caregivers who had cared for their relative for more than 2 years and who had stopped caring for them more than 2 years previously. Fourteen in-depth interviews were conducted and data were collected over 13 months between 2015 and 2017. Data were analysed using the Grounded Theory Method. In addition, this study was approved by the ethics committee of the Institut Universitari d’Investigació en Atenció Primària Jordi Gol. The former caregiver experiences a transition, which begins in the days before the death of their relative and may continue for more than 3 years. Three critical moments in the post-caring transition were found: (1) the post-caring emptiness; (2) the end of the period as a caregiver; and (3) the movement towards a new life. Family and professional support is needed during this transition. Former caregivers experience a transition in the rebuilding of their daily lives; furthermore, former caregivers may be a source of support for other caregivers, which is linked to positive mental health factors. Healthcare organisations need to acknowledge the emotional, psychosocial and psychological health of former caregivers.